Translating Southwestern Landscapes : The Making of an Anglo Literary Region - Goodman, Audrey, 1966- (Book collections on Project MUSE., 2016)
Examines how the Southwest emerged as a symbolic cultural space for Anglos, from 1880 through the early decades of the twentieth century, particularly in the works of amateur ethnographer Charles Lummis, pulp novelist Zane Grey, translator of Indian songs Mary Austin, and modernist author Willa Cather.